The Analysis of Foundry Engineering of Copper Alloys Based on the Research of a Metallurgist Settlement in Szczepidło - Garbacz-Klempka, Aldona; Makarowicz, Przemysław; Tokarski, Tomasz (Foundry Commission of the Polish Academy of Sciences, 2017)
The article presents chosen aspects of foundry engineering of the settlement dwellers, including the archaeometric characteristics and metal science analysis of the artefacts, as well as an attempted reconstruction of the production organization. Discovered in Szczepidło (Greater Poland), the foundry workshop is unique in Central European Bronze Age. This workshop foundry operated roughly XIV-XII Century BC. Its production is evidenced by the presence of markers of the whole production cycle: semi-finished and finished products, production waste, fragments of crucibles and casting ladles with traces of usage, and tools. On this basis the alloys and foundry technologies used have been described. The analysis of foundry technology of copper alloys in the settlement area was carried out by observing the surface and structure of the products, semi-finished artefacts and fragments of crucibles by applying optical microscopy (OM), confocal microscopy (CLSM) and Xray radiography (RT). The investigations of compositions were made by means of the energy dispersive X-ray fluorescence spectroscopy (ED-XRF) and scanning electron microscopy (SEM) coupled with an energy dispersive X-ray analysis system (EDS).
Keywords: non-destructive testing; Archaeometallurgy; Bronze age workshop; Investment casting; Copper alloys; X-ray fluorescence spectroscopy